2021
DOI: 10.1093/mnras/stab1175
|View full text |Cite
|
Sign up to set email alerts
|

Testing the fossil field hypothesis: could strongly magnetized OB stars produce all known magnetars?

Abstract: Stars of spectral types O and B produce neutron stars (NSs) after supernova explosions. Most of NSs are strongly magnetized including normal radio pulsars with B ∝ 1012 G and magnetars with B ∝ 1014 G. A fraction of 7–12 per cent of massive stars are also magnetized with B ∝ 103 G and some are weakly magnetized with B ∝ 1 G. It was suggested that magnetic fields of NSs could be the fossil remnants of magnetic fields of their progenitors. This work is dedicated to study this hypothesis. First, we gather all mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 112 publications
(113 reference statements)
3
12
0
5
Order By: Relevance
“…Modern MHD simulations [22] showed that strong stellar magnetic fields could be formed as a result of stellar merger. Authors [22] found that a star that is born as a result of a merger has a magnetic field of ≈9 kG, which is compatible with values for some strongly magnetised massive stars [21].…”
Section: Formationsupporting
confidence: 54%
See 3 more Smart Citations
“…Modern MHD simulations [22] showed that strong stellar magnetic fields could be formed as a result of stellar merger. Authors [22] found that a star that is born as a result of a merger has a magnetic field of ≈9 kG, which is compatible with values for some strongly magnetised massive stars [21].…”
Section: Formationsupporting
confidence: 54%
“…In general, the absence of magnetars and M7-like sources with P 20 s is indirect evidence of field decay since with an initial surface field B 0 ∼ 10 14 G, a NS can spin down to a period of a few hundred seconds in a few hundred thousand years (a typical age of the M7 sources) if the field is not decaying. Recent examples of population studies of magneto-rotational evolution of initially highly magnetised NSs can be found in [21,119]. These studies demonstrated that rapid field decay in magnetars prevents the formation of bright sources with spin periods longer than those already observed for these objects.…”
Section: Magnificent Sevenmentioning
confidence: 95%
See 2 more Smart Citations
“…Secondly, it was recently noted that there are toofew strongly-magnetized massive stars for simple flux conservation to explain the observed magnetar population (Makarenko et al 2021). A similar challenge exists at lower masses: ∼ 10 % of A/B star show strong surface magnetic fields (Power et al 2007) while ∼ 20 % of their White Dwarf remnants have the 10 5−6 G fields those would produce under flux conservation (Landstreet & Bagnulo 2019).…”
Section: Strong Hidden Fossil Fieldsmentioning
confidence: 99%